2019
DOI: 10.2147/ndt.s195275
|View full text |Cite
|
Sign up to set email alerts
|

<p>Minimally invasive evacuation of spontaneous supratentorial intracerebral hemorrhage by transcranial neuroendoscopic approach</p>

Abstract: Objective Spontaneous supratentorial intracerebral hemorrhage (SSICH) is one of the deadliest diseases, and neuroendoscopic surgery (NE) is a minimally invasive and promising treatment that might improve the functional recovery of patients. This study analyzed patient’s experience with this treatment in terms of safety, efficacy, and surgical technique. Patients and methods Forty-two patients with SSICHs treated by transcranial neuroendoscopic approach were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The surgical methods of SSICH mainly include stereotactic aspiration, neuroendoscopy and craniotomy, which have their advantages and disadvantages [8][9][10][11][12][13] . Stereotactic aspiration was an effective and commonly used method in clinical practice, although its indication was narrow to small and mediumsized stable hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical methods of SSICH mainly include stereotactic aspiration, neuroendoscopy and craniotomy, which have their advantages and disadvantages [8][9][10][11][12][13] . Stereotactic aspiration was an effective and commonly used method in clinical practice, although its indication was narrow to small and mediumsized stable hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic pain syndrome commonly follows an ischemic stroke or hemorrhagic stroke in the thalamic and lateral medullary areas [ 3 , 8 , 9 ]. PS-TP occurs after thalamic stroke with sensory deficits, and it often comes up to 40% in the acute phase following the stroke, e.g., within a month of the stroke [ 10 , 11 , 12 ].…”
Section: Poststroke Thalamic Painmentioning
confidence: 99%
“…It has the advantages of good light, multi angle view, close observation and so on, while has great advantages in hypertensive intracerebral hemorrhage surgery 2 , craniotomy aneurysm clipping surgery 3 , 4 , trigeminal nerve/facial nerve microvascular decompression surgery 6 , and even craniotomy brain tumor surgery. Study 10 has shown that transcranial neuroendoscopic is more than 90% of hematoma removal in intracerebral hemorrhage surgery. Moreover, the side injury is small, the complications are few, and it is safe and effective.…”
Section: Discussmentioning
confidence: 99%